Toripalimab plus chemotherapy in the treatment of metastatic triple-negative breast cancer: a cost-effectiveness analysis - Cai, Hongfu; Huang, Lisheng; Zheng, Zhiwei (Frontiers in Public Health, 2024)
Objective: This study focuses on assessing the cost-effectiveness of incorporating toripalimab alongside chemotherapy for the treatment of patients diagnosed with metastatic triple-negative breast cancer from the perspective of the Chinese healthcare system. Methods: A partitioned survival model was constructed to simulate the costs and health outcomes over the lifetime of patients with mTNBC. Clinical data regarding overall survival, progression-free survival, and treatment-related adverse events were derived from the TORCHLIGHT clinical trials. Incremental cost-effectiveness ratio (ICER) were calculated based on the gains in quality-adjusted life-year (QALY). The willingness-to-pay (WTP) threshold was defined as $39,855.79 per QALY. Additionally, sensitivity analyses were conducted to examine the robustness of the model. Results: The total cost incurred by the group receiving toripalimab was $38,040.62,while the placebo plus chemotherapy was $26,102.07.The utilization of the toripalimab regimen resulted in an increase of 0.74 QALYs and an incremental cost of $11,938.55 compared to the placebo plus chemotherapy group. The ICER was $16133.18/QALY, indicating that toripalimab plus chemotherapy is a cost-effective strategy according to the WTP threshold. Sensitivity analyses confirmed the robustness of the results. Conclusion: This study suggests that the addition of toripalimab to chemotherapy for the treatment of mTNBC is a cost-effective strategy. The findings provide valuable evidence to guide decision-making regarding treatment selection for patients with mTNBC in China.